Effect of low-dose, short-duration creatine supplementation on anaerobic exercise performance - Hoffmann, J. R.; Stout, J. R.; Falvo, M. J.; Kang, J.; Ratamess, N. A. (The Journal of Strength and Conditioning Research, 2005)
To examine the efficacy of a low-dose, short-duration creatine monohydrate supplement, 40 physically active men were randomly assigned to either a placebo or creatine supplementation group (6 g of creatine monohydrate per day). Testing occurred before and at the end of 6 days of supplementation. During each testing session, subjects performed three 15-second Wingate anaerobic power tests. No significant (p > 0.05) group or time differences were observed in body mass, peak power, mean power, or total work. In addition, no significant (p > 0.05) differences were observed in peak power, mean power, or total work. However, the change in the rate of fatigue of total work was significantly (p < 0.05) lower in the creatine supplementation group than in the placebo group, indicating a reduced fatigue rate in subjects supplementing with creatine compared with the placebo. Although the results of this study demonstrated reduced fatigue rates in patients during high-intensity sprint intervals, further research is necessary in examining the efficacy of low-dose, short-term creatine supplementation.